2013
DOI: 10.1182/blood-2013-05-501445
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the alternative pathway of complement in children with hematopoietic stem cell transplant-associated thrombotic microangiopathy

Abstract: Key Points Genetic variations in the alternative pathway of complement may be associated with thrombotic microangiopathy in children receiving HSCT. These findings may guide the development of novel treatment interventions for this poorly understood transplant complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
184
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(191 citation statements)
references
References 30 publications
2
184
2
3
Order By: Relevance
“…8,[10][11][12][13][14][15][16][17][18] These include membranous nephropathy, minimal change disease, and focal segmental glomerulosclerosis. In addition, acute and chronic thrombotic microangiopathy, or 'transplant-associated thrombotic microangiopathy,' has been shown to occur commonly in hematopoietic cell transplant recipients, 8,14,[17][18][19][20][21][22][23][24][25] with smaller reported numbers of membranoproliferative glomerulonephritis, proliferative glomerulonephritis, ANCA-associated glomerulonephritis, and IgA nephropathy. 8,18,[26][27][28][29][30][31][32][33][34][35][36][37] In studies also examining nonglomerular pathology, kidney specimens also show concomitant tubulointerstitial and vascular changes in hematopoietic cell transplant patients.…”
mentioning
confidence: 99%
“…8,[10][11][12][13][14][15][16][17][18] These include membranous nephropathy, minimal change disease, and focal segmental glomerulosclerosis. In addition, acute and chronic thrombotic microangiopathy, or 'transplant-associated thrombotic microangiopathy,' has been shown to occur commonly in hematopoietic cell transplant recipients, 8,14,[17][18][19][20][21][22][23][24][25] with smaller reported numbers of membranoproliferative glomerulonephritis, proliferative glomerulonephritis, ANCA-associated glomerulonephritis, and IgA nephropathy. 8,18,[26][27][28][29][30][31][32][33][34][35][36][37] In studies also examining nonglomerular pathology, kidney specimens also show concomitant tubulointerstitial and vascular changes in hematopoietic cell transplant patients.…”
mentioning
confidence: 99%
“…Expression levels of complement factor H (CFH), CFHrelated 1 and 3 proteins were detected and anti-CFH antibody was not identified in the patient's plasma by western blotting. Typical deletions in the CFH-related genes 3 and 1 observed in patients with aHUS 8 or TA-TMA 4 were not identified by multiplex ligationdependent probe amplification. In our investigation, we failed to show the finding that the dysregulation of the complement system was associated with the development of TA-TMA in this patient.…”
mentioning
confidence: 86%
“…Particularly, prognosis of the TA-TMA with multiorgan impairment is poor because there is no definitive therapy. [1][2][3] The pathogenesis of TA-TMA remains undetermined; however, Jodele et al 4 reported that dysregulation of the complement system may be involved in the pathogenesis of TA-TMA. Eculizumab, a humanized moAb against the complement component C5 that prevents tissue damage by blocking the formation of the membrane attack complex, has been successful in the treatment of paroxysmal nocturnal hemoglobinuria or atypical hemolytic uremic syndrome (aHUS).…”
mentioning
confidence: 99%
“…According to the literature, the prevalence varies between 0% and 74% because it is often not recognized sufficiently. 70 TA-TMA has a high mortality rate reaching almost 100%.…”
Section: Thrombotic Microangiopathymentioning
confidence: 99%
“…71 It was claimed that complement dysregulation has also effect on the disease pathogenesis. 70 In the historical process, Cho BS et al recently suggested a new guideline by restocking previous guidelines in addition to diagnostic criteria defined by Bone Marrow Transplant Clinical Trials Network (BMT-CTN) and International Working Group (IWG) ( Table-1). …”
Section: 71mentioning
confidence: 99%